POLA KONSUMSI IKAN PADA ANAK BALITA DI NAGARI TARUANG-TARUANG KECAMATAN RAO KABUPATEN PASAMAN - Apriani, rina; Yuliana, Yuliana; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2012)
This study aims to analyze the consumption patterns of fish that includes the frequency of fish consumption, the type of fish consumed, the amount of fish consumed, forms processing, methods of cooking fish, reasons to eat fish and protein content of the fish consumed. Type of research is descriptive. Techniques in the determination of the sample is proportional random sampling. The population is children under five. The samples in this study were 35 children under five. Data collection tool that interview, format Questionari Food Frequency (FFQ) and the format of 2 x 24-hour recall. The results showed that the frequency of fish consumption among children under five is 3-4 days / week. Types of fish that frequent consumption of fish is mujair, nila and teri. The average number of fish consumed 63.75 g / hr. Forms processing and cooking of fish is often done curing and frying. Reasons parents give to children under five fish because fish is good for health and growth of children. The average protein content of the fish consumed 10-20 grams / day.